Evaluation of Carbonic Maceration Effect as a Pre-Treatment on the Drying Process of Strawberry - Muhammed Mustafa Ozcelik; Gulcan Ozkan; Erkan Karacabey (Agriculture, 2022)
In the last decade, organic-based food materials have taken an increasing marketing share due to consumers’ interests. Strawberry is one of the world’s most important berry crops, with growing production. This study aimed to evaluate the drying process of organic strawberries and to determine the influences of process conditions on drying characteristics. To improve drying performance, carbonic maceration (CM) was investigated as a pre-treatment. The experimental design and the optimization of the drying with pre-treatment conditions were performed using statistical modeling (response surface method (RSM), central composite design (CCD)). Using the RSM, dependent variables such as drying time, total phenolic compound, antioxidant capacity, ascorbic acid concentration, and hue value were optimized as a function of operating conditions of CM pre-treatment and following the drying process. The results indicated that drying performance varied depending on drying temperature as well as process conditions of CM. Drying time was reduced by more than 30% with CM treatment compared to control. Furthermore, ascorbic acid content, antioxidant activity, and surface color of dried samples were protected better in the case of CM-pre-treated strawberries. Results showed that the optimum drying temperature, maceration pressure, maceration temperature, and maceration time parameters were 64.8 °C, 3.54 bar, 4.2 °C, and 4 h, respectively. The high potential of CM should be considered in terms of process improvement and product quality for drying processes. Thus, this study provides key outcomes in this respect. According to the obtained results, the CM was assessed as a promising technique applied before the drying of organic strawberries.